2016
DOI: 10.1016/j.acalib.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Use It or Lose It? A Longitudinal Performance Assessment of Undergraduate Business Students' Information Literacy

Abstract: At a large, public, Midwestern, American university, business librarians teach a required, one-credit information literacy course geared towards lower-division students in the school of management. In order to determine the lasting effects of the course, a longitudinal study of individual students' performance on three pre/post-test surveys was conducted across a set of management courses. The first course, a required information literacy class, was generally taken in the lower-division. The second course, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Problembased learning (PBL) and inquiry-based learning (IBL) are subsets of active learning and PBL is integrated into IBL (Spronken-Smith et al, 2007;Spronken-Smith, 2012). Research findings suggest that, regardless of pedagogical methods used, students' overall information literacy knowledge and skills were improved by participating in teaching interventions (Argelagós et al, 2022;Stonebraker and Fundator, 2016). Dolničar et al (2017) employed three teaching methods for three credit-bearing information literacy courses at a university in Slovenia and compared the effectiveness of the methods in improving information literacy skills of the students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Problembased learning (PBL) and inquiry-based learning (IBL) are subsets of active learning and PBL is integrated into IBL (Spronken-Smith et al, 2007;Spronken-Smith, 2012). Research findings suggest that, regardless of pedagogical methods used, students' overall information literacy knowledge and skills were improved by participating in teaching interventions (Argelagós et al, 2022;Stonebraker and Fundator, 2016). Dolničar et al (2017) employed three teaching methods for three credit-bearing information literacy courses at a university in Slovenia and compared the effectiveness of the methods in improving information literacy skills of the students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In higher education, a variety of pedagogical approaches have been employed to improve students' information literacy in engineering (Liu, 2021), business (Stonebraker and Fundator, 2016), life sciences and health study (Dolničar et al, 2017), sports and exercise (Walton and Hepworth 2011), and library and information science (Lamb, 2017). Students received instructions online (Argelagós et al, 2022;Lamb, 2017), face-to-face (Dolničar et al, 2017), and blended (Walton and Hepworth, 2011) methods through one-shot sessions (Liu, 2021), dedicated credit-bearing courses (Argelagós et al, 2022;Dolničar et al, 2017;Lamb, 2017;Stonebraker and Fundator, 2016;Walton and Hepworth 2011), and embedded-curriculum (Adams et al, 2016;Johnson-Grau et al, 2016;Wang, 2011). There was a lack of research that reported curriculum-embedded information literacy instructions in library and information science schools.…”
Section: Literature Reviewmentioning
confidence: 99%